Factors associated with cervical cancer screening: results from cross-sectional surveys in Kenya and Malawi - Corrina Moucheraud; Symon Chibaka; Ginger Golub; Pericles Kalande; Amos Makwaya; Eric Ochieng; Vitalis Ogutu; Khumbo Phiri; Sam Phiri; Risa M. Hoffman (BMC Public Health)
Abstract Background Cervical cancer screening is an essential public health intervention, and critical to meeting the Global Strategy for Cervical Cancer Elimination goals – yet most women in low- and middle-income countries are never screened. There is a need to understand context-specific factors that facilitate or prevent women from engaging in screening. Methods This analysis leverages data collected in 2022–2023 from a national mobile phone-based survey in Kenya and from a household survey conducted in three districts of Malawi. Informed by the Health Belief Model, we assess whether women’s reported cervical cancer screening history (ever or never screened) was associated with their perceived susceptibility (awareness of cervical cancer risk factors), perceived severity (knowing someone who was affected by cervical cancer), perceived barriers (access to services), perceived benefits (trust in information about cervical cancer prevention), self-efficacy (engagement in other preventive health behaviors), and cues to action (speaking with others about cervical cancer prevention). Results Ever-screening for cervical cancer was reported by 49.7% of the 736 Kenyan respondents and 42.5% of the 261 Malawian respondents. There were few associations between women’s demographic or socioeconomic characteristics and screening history. The strongest associations were seen for cues to action (women who had spoken about cervical cancer with health workers had 1.88 the adjusted risk ratio for screening in Kenya [95% CI 1.59, 2.24] and 1.89 the adjusted risk in Malawi [95% CI 1.41, 2.54] compared to women who never had these conversations); and for knowing someone who had, or who had died due to, cervical cancer (aRR 1.34 and 1.30 respectively in Kenya, and aRR 2.03 and 1.46 respectively in Malawi). In both countries, self-efficacy was also associated with screening, as was perceived severity in both countries (i.e., knowing someone who had, or who had died due to cervical cancer, which was reported by many Kenyan and Malawian respondents). In Kenya, knowledge of cervical cancer risk factors was also associated with women’s screening history, as was access to other preventive health services in Malawi. Conclusions These results suggest promising areas for interventions aiming to increase cervical cancer screening in these contexts: encouraging health workers to discuss screening with eligible women, leveraging women’s peers who have been affected by cervical cancer, and promoting screening during other preventive health services.